Dichotomy or Continuum: Grice's Distinction between Natural and Nonnatural Meaning - Mehmet Hilmi Demir (Felsefe Dünyası)
Grice (1957), in his theory of meaning, introduced a distinction between two different types of meaning: nonnatural meaning and natural meaning. Grice’s distinction has been put to use in other areas of philosophy as well. Most famously, Dretske (1981, 1986) used Grice’s distinction in his naturalized epistemology. Scarantino and Piccinini (2010) offered a probabilistic alternative for semantic theories of information based on Grice's distinction. In both Dretske’s and Scarantino and Piccinini’s works, Grice’s distinction is assumed to form a dichotomy. This dichotomous nature, I claim, is at the root of some of the problems that afflict Dretske’s information-based naturalized epistemology and Scarantino and Piccinini’s probabilistic approach to information. In this paper, I suggest a revised version of Grice's distinction. In this revised version, instead of a dichotomy, natural and nonnatural meaning categories form a continuity, allowing overlapping and mixed intermediary categories between natural and nonnatural meaning. This continuous version, I further claim, provides more resources for avoiding some of the problems that afflict Dretske’s naturalized epistemology and Scarantino and Piccinini’s probabilistic approach to information.